Biology teachers’ preferences and key factors in adopting learning technology - Ahmad Kamal Sudrajat; Agung Wijaya Subiantoro; M. Ikhsan Al Ghazi (University of Muhammadiyah Malang, 2025)
Technology development has changed students' characteristics and learning needs. As facilitators of student learning, teachers should be able to use learning technology effectively in their classrooms. This study aimed to examine teacher preferences in using learning technology and explore key factors for using learning technology. This study used a survey design conducted on biology teachers in Yogyakarta, Indonesia. A total of 47 biology teachers participated in this study. The survey was conducted to gather information regarding demographic data, the frequency of technology usage, and teachers' preferences in utilizing technology. The preferences for technology use encompass two main aspects: teachers' experiences with technology and their future expectations. The results indicate that teachers are more interested in using learning technology on conceptual materials. Teachers suggest the development of application-based biology learning media on cell phones or laptops. The main factor for teachers to use technology is that they have sufficient basic knowledge of the learning technology they will use. Teaching experience and frequency of using technology do not affect the teacher’s factor in choosing technology. The government and universities can use the results of this study as a basis for further development of learning technology. Shifts in learning patterns and technological advances need to get attention from the government so that teacher training programs, especially those related to learning technology, can be carried out appropriately and effectively.